Effect of surface nanostructuring in solution treated and thermally aged condition on LCF life of AA7075 - Pandey V.; Singh M.K.; Basu J.; Chattopadhyay K.; Srinivas N.C.S.; Singh V. (My University, 2025)
Low cycle fatigue (LCF) behavior of the AA7075 was studied in the solution treated-ultrasonic shot peened and the peak aged (ST-USSP-PA) condition and was compared with that of the peak aged and ultrasonic shot peened (PA-USSP) as well the peak aged-ultrasonic shot peened and stress relieved (PA-USSP-SR) condition, studied earlier. LCF tests were carried out under fully reversed axial strain control at different total strain amplitudes (Δεt/2) from ±0.38% to ±0.60%. LCF life was highest in the ST-USSP-PA followed by the PA-USSP and PA-USSP-SR conditions. It was found that nanostructure of comparable size (~22 nm) was developed up to a depth of ~50 μm in all the three conditions, however, there was much variation in the type, size, distribution and number density of the metastable of η precipitates in the three conditions. While the size of the strengthening precipitates η′ was ~20 nm in the ST-USSP-PA, it was much smaller (~10 nm) in the other two conditions. High resolution TEM examination revealed high density of dislocations in the matrix and also within the equilibrium η precipitates in the PA-USSP condition whereas dislocations were not observed in η precipitates of the PA-USSP-SR and ST-USSP-PA conditions. Highest fatigue life in the ST-USSP-PA condition is attributed to more homogeneous distribution, larger size and higher volume fraction of the strengthening precipitates η′ and consequent increase in the resistance against fatigue crack initiation. © 2020 Elsevier B.V.